A responsabilidade dos administradores na insolvência - Graça, Beatriz Bizarro Pisani da (2019)
The subject of insolvency assumes great relevance in the Portuguese society. In our country, a high number of companies ends up in ruin. One of the causes of this problem is the irresponsible behaviour of our companies’ administrators that jeopardize their survival. We have to face with the need to see how and to what extent the administrators that cause the insolvency situation or make it worse can be held responsible for it. In order to answer this question, we will analyse the entire regime of the accountability of the administrators present in the CIRE, as well as the interconnections, which proved to be necessary, to make between this diploma and the CSC.